Heparin, Protamine and Polybrene - Britten, Anthony (Thrombosis and Haemostasis, 1965)
The effects of incubating heparin, protamine or Polybrene with plasma were studied. All three drugs cause rapid loss of factor V from decalcified plasma, while Polybrene also accelerates the loss of factor VIII activity. These changes are related to temperature, the period of incubation and the dose of the drug used, and can be partially prevented by inclusion of neutralizing doses of the appropriate antagonist in the incubation mixture.The implications of these findings are discussed.